2020
DOI: 10.1016/j.cub.2020.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont Digestive Range Reflects Host Plant Breadth in Herbivorous Beetles

Abstract: Highlights d Stammera genomes are structurally conserved across Cassidinae species d Symbiont pectinases complement the host's endogenous cellulases and xylanases d Stammera differentially encode pectinases in their reduced genomes d Symbiont pectinolytic range reflects host plant breadth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 90 publications
(149 reference statements)
1
86
0
1
Order By: Relevance
“…This physiological contribution represents a significant fitness benefit in dry habitats like mass grain storage 42 . Here, we demonstrated that the genome of S. silvanidophilus experienced a drastic erosion, resulting in a genome of 308 kbp in size and a strongly AT-biased nucleotide composition (16.2% GC), akin to what has been described for other obligate intracellular 47 , 71 , 72 or extracellular insect symbionts 73 76 .…”
Section: Discussionmentioning
confidence: 66%
“…This physiological contribution represents a significant fitness benefit in dry habitats like mass grain storage 42 . Here, we demonstrated that the genome of S. silvanidophilus experienced a drastic erosion, resulting in a genome of 308 kbp in size and a strongly AT-biased nucleotide composition (16.2% GC), akin to what has been described for other obligate intracellular 47 , 71 , 72 or extracellular insect symbionts 73 76 .…”
Section: Discussionmentioning
confidence: 66%
“…The critical regulatory decision points thus likely depend less on any decisive nutrient or nutrient-targeting enzyme (e.g. a pectinase) (58), but rather on the decisive cues (e.g. volatile semiochemicals (54, 59)) that enable ants to detect the cultivar’s immediate nutritional needs and then adjust provisioning.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of symbionts on their individual hosts has both ecological and evolutionary implications. For instance, symbionts can alter the capacity of their host to colonize new ecological niches or change the direction of sexual selection (Dyson and Hurst, 2004; Salem et al , 2020). They may drive host evolution, both to accommodate symbionts with positive effects (for instance, bacteriomes) (Buchner, 1965) and suppress negative symbiont characteristics (Hornett et al 2006).…”
Section: Introductionmentioning
confidence: 99%